2018
DOI: 10.3390/ijerph15122640
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction of Physicians Working in Polish Hospitals—A Cross-Sectional Study

Abstract: Physician satisfaction is a multidimensional concept associated with numerous factors. The objectives of the study were to evaluate the satisfaction of physicians practicing in hospitals in Poland and to identify factors associated with higher levels of satisfaction. A quantitative, cross-sectional survey of Polish hospitals was conducted between March and June 2018. All doctors working in the hospitals invited to the study were asked to fill in an online survey. Fifteen hospitals were included: seven general,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…In the study by Tyssen et al, 90% of physicians in Canada and Norway, and 84% of U.S. doctors, defined their level of job satisfaction as "at least somewhat satisfied" [18]. A cross-sectional survey performed by Domagała et al among physicians working in Polish hospitals showed that the mean level of career satisfaction, evaluated using a 6-point scale, was 4.1±0.69 pts [19]. In this study, the authors observed a significantly higher professional satisfaction level (p < 0.001) among physicians working in the private area compared to the public one, which also varied between the surveyed doctors depending on the place and type of primary employment.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Tyssen et al, 90% of physicians in Canada and Norway, and 84% of U.S. doctors, defined their level of job satisfaction as "at least somewhat satisfied" [18]. A cross-sectional survey performed by Domagała et al among physicians working in Polish hospitals showed that the mean level of career satisfaction, evaluated using a 6-point scale, was 4.1±0.69 pts [19]. In this study, the authors observed a significantly higher professional satisfaction level (p < 0.001) among physicians working in the private area compared to the public one, which also varied between the surveyed doctors depending on the place and type of primary employment.…”
Section: Discussionmentioning
confidence: 99%
“…We are presenting a multidimensional questionnaire that has been adapted into Polish through a rigorous multistage process [19], and that has very good psychometric characteristics among physicians working in Polish hospitals. Moreover, the 4CornerSAT questionnaire is available in four different languages and countries [14,[18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…All physicians working in 15 Polish hospitals were invited to participate in a survey between March and June of 2018 [21]. Participants completed the questionnaire online, with the option to participate on paper if they experienced problems completing the online version.…”
Section: Samplementioning
confidence: 99%
See 2 more Smart Citations